Improving Learning Experience of Probability and Statistics using Multimedia System - Krishnasamy, Sivapoorani; Ling, Lew Sook; Kim, Tan Choo (International journal of emerging technologies in learning, 2020)
In this 21st century, the rapid development and growth of technology has en-hanced teaching and learning experiences effectively in the delivery of learning contents. However, there are still lacking of integration of information technology (IT) in teaching although IT is pervasive. This study was conducted to determine the relationship between Information Technology (IT) capabilities, learning expe-riences and performance of teaching and learning Mathematics. Multimedia Prob-ability and Statistics System (MMPASS) was developed and used as the IT ca-pability framework to determine the effects on students’ learning experiences to-wards performance of Mathematics. The sample size of this study were 66 stu-dents of foundation programme who are taking Probability and Statistics subject. The subject was delivered to two different groups of students; “with” and “with-out” the MMPASS. Findings showed that students’ learning experiences and performances of their academic achievement have been improved by using MMPASS. Hence, MMPASS is one of the effective IT capability in improving performance of teaching and learning Mathematics.